2021
DOI: 10.18502/ijps.v16i1.5383
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Outpatient: Community Mental Health Centers (CMHCs)

Abstract: Objective: The Iranian Mental Health Survey (IranMHS) in 2011 has demonstrated that almost 1 out of 4 adult individuals suffer from psychiatric disorders; however, more than two-thirds are left unrecognized and untreated and many of the services have poor quality of care. In this paper we present our experience in developing and employing community-based mental health services through community mental health centers (CMHCs), which has been incorporated in Iran's comprehensive mental and social health services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For example In Iran, 18% of the health organization's budget is spent on mental health problems in mental hospitals, while patients with a history of admission in psychiatric hospitals are the minority of people with mental health condition [ 21 ]. CMHC as a specialized outpatient providing mental health care was found to have positive impacts on the cost effectiveness and efficacy of in Iran and other countries [ 15 , 17 , 22 , 23 ]. Five years after the establishment of CMHC in Iran, Sharifi et al suggested that skilled staff, a better source of funding, and more integration into the healthcare system can enhance the performance and efficacy of CMHC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example In Iran, 18% of the health organization's budget is spent on mental health problems in mental hospitals, while patients with a history of admission in psychiatric hospitals are the minority of people with mental health condition [ 21 ]. CMHC as a specialized outpatient providing mental health care was found to have positive impacts on the cost effectiveness and efficacy of in Iran and other countries [ 15 , 17 , 22 , 23 ]. Five years after the establishment of CMHC in Iran, Sharifi et al suggested that skilled staff, a better source of funding, and more integration into the healthcare system can enhance the performance and efficacy of CMHC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aftercare focuses on treatment and follow-up for patients with severe mental illnesses, including those with a history of psychiatric hospitalization, and offers home care and telephone follow-up. CMHCs also provide mental health education for patients and their families [ 14 17 ]. Patients typically come to CMHCs via referral from PHCs or psychiatric hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a small community trial in three districts in Iran, SERAJ was associated with improved mental health literacy and decreased prevalence of mental disorders in the intervention districts ( 33 ). After 6 years, the program has been expanded to 23 districts, however, the SERHJ program has not yet been fully scaled to a national level, despite the promising outcomes during the trial ( 34 ).…”
Section: Suicide Prevention Efforts and Challenges In Iranmentioning
confidence: 99%
“…Based on the transition of mental health care in Iran within about 2 decades, from introducing basic mental health care in PHC to the experience of communitybased mental health centers (CMHC) for urban areas [7], a new socio-mental health service model, with two basic and advanced service strata, has been so far proposed. The given model has been piloted in eight cities in this country over the last 5 years.…”
Section: Introductionmentioning
confidence: 99%